Hybrid modeling of quasi-particles: Algebra, Fock space and condensation. (October 2018) - Chung, Won Sang; Algin, Abdullah
Highlights: A new quasi-particle algebra is proposed. A unified framework for the intermediate-statistics is introduced. The low-temperature behavior of the hybrid-type quasi-particle gas is studied. The condensation characteristics of the hybrid-type quasi-particle gas is discussed. Abstract: In this study, we first introduce a new quasi-particle algebra, which enables us to effectively describe a unified framework for both bosons and fermions. We then study general thermodynamical and statistical properties of a hybrid-type gas model of these quasi-particles. In this context, we specifically focus on the conditions under which the hybrid-type quasi-particle gas condensation would occur in the present model. The results obtained in this work reveal that the present gas model of quasi-particles can be used to approximate non-linear behavior observed in composite particle systems such as in studies on the phenomenon of high- Tc superconductivity in a given material.